2014
DOI: 10.3109/09513590.2014.975683
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum cytokines-related Th1/Th2/Th17 concentration in patients with postmenopausal osteoporosis

Abstract: Our experiments have confirmed the roles of IL-17 in the pathogenesis of postmenopausal osteoporosis and in the promotion of bone resorption. Targeted therapy of IL-17, IFN-γ, and IL-4 may be beneficial in the treatment of patients with postmenopausal osteoporosis. Our experiments have also confirmed the roles of IFN-γ and IL-4 in the pathogenesis of postmenopausal osteoporosis and in the inhibition of bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 46 publications
(42 reference statements)
4
41
0
4
Order By: Relevance
“…The change in circulating IL-17 level in the context of estrogen deprivation was frequently reported in animal studies [18] . Our study observed a significant rise in circulating IL-17 level in osteoporotic postmenopausal women, which was consistent with recent findings [19,25,26] . IL-17 can directly promote the production of RANKL by osteoblasts [17,18,27,28] .…”
Section: Discussionsupporting
confidence: 82%
“…The change in circulating IL-17 level in the context of estrogen deprivation was frequently reported in animal studies [18] . Our study observed a significant rise in circulating IL-17 level in osteoporotic postmenopausal women, which was consistent with recent findings [19,25,26] . IL-17 can directly promote the production of RANKL by osteoblasts [17,18,27,28] .…”
Section: Discussionsupporting
confidence: 82%
“…Another factor responsible for the bone loss induced by estrogen deficiency is IL-17, the signature cytokine of Th17 cells (47), which are an osteoclastogenic subset of CD4 + T cells (45,46). Intriguingly, postmenopausal women with osteoporosis exhibit elevated levels of serum IL-17 (66)(67)(68). In mice, ovx expands Th17 cells by promoting the differentiation of naive CD4 + T cells into mature Th17 cells (69), a phenomenon driven by cytokines such as TGFβ, IL-6, IL-1β, and TNF (43,44,47,70) -factors that are all disregulated by estrogen deficiency (25).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the function of adipose tissue as an endocrine gland which secretes several cytokines, this association has frequently been attributed to central obesity (3). Indeed, some studies have regarded inflammation as a risk factor for osteoporosis (4,5). However, the precise mechanism underlying the role of inflammation as well as the association between obesity, inflammation and osteoporosis has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%